What was Glaucoma Called before the 20th Century?. (January 2015) - Leffler, Christopher T.; Schwartz, Stephen G.; Giliberti, Francesca M.; Young, Matthew T.; Bermudez, Dennis
Glaucoma involves a characteristic optic neuropathy, often with elevated intraocular pressure. Before 1850, poor vision with a normal eye appearance, as occurs in primary open-angle glaucoma, was termed amaurosis, gutta serena, or black cataract. Few observers noted palpable hardness of the eye in amaurosis. On the other hand, angle-closure glaucoma can produce a green or gray pupil, and therefore was called, variously, glaucoma (derived from the Greek for glaucous, a nonspecific term connoting blue, green, or light gray) and viriditate oculi. Angle closure, with palpable hardness of the eye, mydriasis, and anterior prominence of the lens, was described in greater detail in the 18th and 19th centuries. The introduction of the ophthalmoscope in 1850 permitted the visualization of the excavated optic neuropathy in eyes with a normal or with a dilated greenish-gray pupil. Physicians developed a better appreciation of the role of intraocular pressure in both conditions, which became subsumed under the rubric "glaucoma".